Manual of pediatric allergy - Nagaraju, K. (New Delhi : Jaypee Brothers Medical Publishers (P) Ltd, 2015)
This manual is a practical guide to paediatric allergy bringing clinicians fully up to date with the most recent advances in the field
Approach to allergic child / Major K. Nagaraju -- Pathophysiology of sensitization and allergy / Mahesh PA -- Diagnosis of allergic diseases / Major K. Nagaraju -- Atopic dermatitis / Major K. Nagaraju -- Urticaria and angioedema / Major K. Nagaraju -- Cow's milk allergy / Major K. Nagaraju -- Food allergy / Major K. Nagaraju -- Anaphylaxis / Major K. Nagaraju -- Ocular allergies / Srinivas K. Rao, Major K. Nagaraju -- Clinical features and diagnosis of allergic rhinitis / Major K. Nagaraju -- Treatment of allergic rhinitis / Major K. Nagaraju -- H1 antihistamines in pediatric practice / Major K. Nagaraju -- Genetics of allergy and asthma / Esra Birben, Cansin Sackesen, Omer Kalayci -- Preschool asthma / D. Vijayasekaran -- Diagnosis of asthma / NC Gowrishankar -- Treatment of asthma in children / D. Vijayasekaran -- Acute asthma exacerbations / George V. Guibas, Michael Makris, Nikolaos G. Papadopoulos -- Management of acute asthma / Somu Sivabalan -- Difficult to treat asthma / H. Paramesh -- Drug allergy / Major K. Nagaraju -- Allergens / Major K. Nagaraju, N. Karthik -- Environment and respiratory allergies / H. Paramesh -- Allergen specific immunotherapy / Major K. Nagaraju -- Approach to primary immunodeficiency diseases / Major K. Nagaraju -- Vitamin D and allergy / Major K. Nagaraju, N. Karthik -- Drugs commonly used in allergy and asthma / Major K. Nagaraju, N. Karthik -- Selected lab values in allergy and immunology / Major K. Nagaraju -- Devices in allergy and asthma / Major K. Nagaraju, N. Karthik
Includes bibliographical references and index
1 13
Keywords: Allergy in children